Uso da ultrassonografia para avaliação do volume gástrico após ingestão de diferentes volumes de solução isotônica - Bisinotto, Flora Margarida Barra [UNESP]; Naves, Aline de Araújo; Lima, Hellen Moreira de; Peixoto, Ana Cristina Abdu; Maia, Gisele Caetano; Resende Junior, Paulo Pacheco; Martins, Laura Bisinotto; Silveira, Luciano A. Matias da (Elsevier, 2017)
Background and objectives The current preoperative fasting guidelines allow fluid intake up to 2 hours before surgery. The aim of this study was to evaluate the gastric volume of volunteers after an overnight fast and compare it with the gastric volume 2 hours after ingestion of 200 and 500 mL of isotonic solution, by means of ultrasound assessment. Method Eighty volunteers underwent gastric ultrasound at three times: after 8 hours of fasting; 2 hours after ingestion of 200 mL isotonic saline, followed by the first scan; and on another day, 2 hours after ingestion of 500 mL of the same solution after an overnight fast. The evaluation was quantitative (antrum area and gastric volume, and the ratio of participants’ gastric volume/weight) and qualitative (absence or presence of gastric contents on right lateral decubitus and supine positions. A p‐value < 0.05 was considered significant). Results There was no difference in quantitative variables at measurement times (p > 0.05). Five volunteers (6.25%) had a volume/weight over 1.5 mL.kg−1 at fasting and 2 hours after ingestion of 200 mL and 6 (7.5%) after 500 mL. Qualitatively, the presence of gastric fluid occurred in more volunteers after fluid ingestion, especially 500 mL (18.7%), although not statistically significant. Conclusion Ultrasound assessment of gastric volume showed no significant difference, both qualitative and quantitative, 2 h after ingestion of 200 mL or 500 mL of isotonic solution compared to fasting, although gastric fluid content has been identified in more volunteers, especially after ingestion of 500 mL isotonic solution.
Use of ultrasound for gastric volume evaluation after ingestion of different volumes of isotonic solution
Keywords: Bronchoaspiration; Gastric ultrasound; Preoperative fasting